Development of a blended communication training program for managing medically unexplained symptoms in primary care using the intervention mapping approach. Issue 5 (May 2022) - Houwen, Juul; de Bont, Olga A.; Lucassen, Peter LBJ; Rosmalen, Judith G.M.; Stappers, Hugo W.; olde Hartman, Tim C.; van Dulmen, Sandra
Highlights: GP training how to communicate with patients with MUS is limited. We developed, implemented and evaluated an evidence-based training program for GP residents focused on patients with MUS. GP residents greatly appreciated the blended character. After attending the training program, GP residents reported increased self-efficacy. GP residents indicated they learned several skills in the management of MUS. Abstract: Background: General practice (GP) training in how to communicate with patients with medically unexplained symptoms (MUS) is limited. Objective: Development, implementation and evaluation of an evidence-based communication training program for GP residents focused on patients with MUS in primary care. Methods: We used the intervention mapping (IM) framework to systematically develop the MUS training program. We conducted a needs assessment to formulate change objectives and identified teaching methods for a MUS communication training program. Next, we developed, implemented and evaluated the training program with 46 residents by assessing their self-efficacy and by exploring their experiences with the training. Results: The resulting program is a blended training with an online course and two training days. After attending the training program, GP residents reported significantly higher self-efficacy for communication with patients with MUS at four weeks follow up compared to baseline. Furthermore, GP residents experienced the training program as useful and valued the combination of the online course and training days. Conclusion and practice implications: We developed an evidence-based communication training program for the management of patients with MUS in primary care. Future research should examine the effect of the training on GP residents' communication skills in MUS consultations in daily practice.